PENGARUH BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG OLEH MAHASISWA UNIVERSITAS X - Adijaya, Abraham (LP2M Institut Teknologi dan Bisnis Asia Malang, 2016)
Currently existing business competition is not only limited to the quality of products, technology products, and display products, but also about the brand used in the product that can cause an image to consumers. Brand is the label that carries meaning and associations as well as a mirror of promise communicated by the producer to the consumer on the quality of products or services that have been produced. This study aims to determine whether the brand awareness, brand association, perceived quality, brand loyalty and other proprietary brand assets Samsung has a positive contribution to brand equity Samsung, knowing which variable dominant contributes positively to brand equity Samsung, and find out whether brand equity Samsung influence the purchasing decisions of Samsung smartphone products. By using principal component analysis and simple linear regression analysis, the result is Samsung’s brand awareness, brand association, perceived quality, brand loyalty, and other proprietary brand assets are able to contribute positively to the Samsung brand equity. Samsung's brand loyalty is the dominant variable that contributes positively to the Samsung brand equity. Samsung's brand equity have positive significant influence on purchasing decisions Samsung smartphone products.